Peran Komunitas Uluwatu dalam Menghadapi Komersialisasi - Maharani, Ni Made Ayundha Dyah; Dewi, Ni Luh Yulyana (Intitut Agama Islam Nasional Laa Roiba Bogor, 2026)
The phenomenon of tourism commercialization in the Pura Luhur Uluwatu area highlights a tension between economic interests and the preservation of sacred cultural values. The temple, which serves as a Hindu place of worship as well as a popular tourist destination, presents significant challenges for the local community in maintaining a balance between religious values and the demands of modern tourism. This study aims to analyze the role of the Uluwatu community in addressing tourism commercialization pressures and to explore how traditional societies preserve cultural values through local wisdom and inherited social systems. The research employs a literature review method by examining relevant academic sources such as journals, books, and research reports on cultural commercialization, community participation, and sustainable tourism management in Bali. The findings reveal that the Uluwatu community plays a vital role in protecting the sanctity of the area through the enforcement of awig-awig (customary law), social monitoring, and participatory communication among residents to balance economic and spiritual interests. Moreover, the active involvement of the government, tourism operators, and visitors is crucial in promoting ethical and sustainable tourism management in this sacred area.